The knowledge of dietary rules among patients with diabetes - Świrska, Joanna; Fedurek, Dominika; Zwolak, Agnieszka; Dudzińska, Marta; Łuczyk, Robert Jan; Daniluk, Jadwiga; Tarach, Jerzy (Journal of Education, Health and Sport, 2017)
Introduction: The incidence of diabetes increases in Poland and all over the world. Diet is an integral element of diabetes therapy. The knowledge of dietary rules and compliance with them facilitates body mass reduction and improves metabolic parameters of the body thus preventing diabetes’ complications development. Aim: The aim of the study was to evaluate the knowledge of dietary rules among diabetic patients. Material and methods: The study included 50 patients with recognized diabetes who were hospitalized in SPSK-4 hospital in Lublin from January to May, 2016. In the study the diagnostic survey was applied. Results: The knowledge of basic dietary rules in diabetes among the majority of surveyed diabetic patients (64%) was unsatisfactory. The most significant deficit included lack of acquaintance with glycemic index and carbohydrate exchanges thus making it impossible to make use of them in preparing everyday meals. The knowledge of the surveyed patients depended on their educational status, place of residence and age. Unsatisfactory knowledge was found among 82% of patients with primary education vs. 40% with higher education, in 80% with countryside residence vs. 53% residing in town and in 80% of patients aged 31-40 and 41-55 years vs. 50% aged 18-30. Conclusion: Dietary education is a necessary element of diabetes therapy. Educating patients about diabetic diet should be repeated regularly as even patients with long-standing diabetes history have unsatisfactory knowledge about the dietary rules. Preferably, educating should be individual and adjusted to patient’s age and education.